Mechanical Performance of the Phosphogypsum Baking-free Bricks - Guo, Xiaoyu; Mao, Yajing; Pei, Lizhai; Fan, Chuangang (Current Materials Science, 2021)
Background: A large amount of phosphogypsum occupies the land and causes environmental pollution. It is of great research significance and urgency to the utilization of the phosphogypsum. Methods: The influence of the ratio of the cementing materials and phosphogypsum (C/P ratio) on the compressive strength, water absorption, softening coefficient and freeze-thaw stability of the phosphogypsum baking-free bricks was investigated. The consolidation process of the phosphogypsum baking-free bricks was analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Results: XRD patterns show that the phosphogypsum baking-free bricks curved for 28 d are mainly composed of monoclinic CaSO4·2H2Oand hexagonal Ca6Al2(SO4)3(OH)12·26H2O (Aft) phases. SEM observation shows that the phosphogypsum bricks consist of Aft nanorods and irregular microscale particles. The softening coefficient, water-resistant performance and freezethaw stability of the phosphogypsum baking-free bricks remarkably decrease with decreasing the C/P ratio. 28 d compressive strength decreases from 26.42 MPa to 15.58 MPa with the change of the C/P ratio from 1:1 to 1:2.5. The optimal ratio of the cementing materials and phosphogymsum is 1:1. The phosphogypsum baking-free bricks exhibit good stability after 18 freeze-thaw cycles. Conclusion: Phosphogypsum baking-free bricks were prepared by natural curing process using phosphogypsum as the raw materials, cement, slag, fly ash and silica fume as the cementing materials. The phosphogypsum baking-free bricks exhibit great application in the field of building materials.
Keywords: X-ray diffraction